Efficacy and safety of toripalimab combined with doxorubicin as first-line treatment for metastatic soft tissue sarcomas: an observational study. Issue 9 (October 2021) - Liu, Zhiyong; Liu, Cuiping; Yao, Weitao; Gao, Songtao; Wang, Jiaqiang; Zhang, Peng; Ge, Hong
Abstract : Programmed cell death protein 1 (PD-1) inhibitors have demonstrated promising activity among patients with advanced soft tissue sarcomas (STS) in phase II trials. The purpose of this study was to assess the efficacy and safety of toripalimab (a novel PD-1 inhibitor) combined with doxorubicin as first-line treatment in patients with metastatic STS between December 2018 and September 2019. A total of 30 patients with metastatic STS were included and followed up retrospectively. One patient had complete response (CR), 10 patients obtained partial response, and 13 patients achieved stable disease. The objective response rate was 36.7% and the disease control rate was 80%. The median progression-free survival (PFS) was 8 months (95% CI: 6.30–10.64). The most frequent any grade adverse events were nausea (66.7%), fatigue (60%), and vomiting (40%). Neutropenia (20%) was the most common grade 3/4 adverse events, followed by leucopenia (13.3%) and febrile neutropenia (6.7%). No death related to treatment was observed during the drugs administration. Toripalimab combined with doxorubicin is effective in patients with metastatic STS as first-line treatment with manageable adverse events.